Craft Sciences (Göteborg studies in conservation / Acta Universitatis Gothoburgensis, 2022)
The field of ‘Craft Sciences’ refers to research conducted across and within different craft subjects and academic contexts. This anthology aims to expose the breadth of topics, source material, methods, perspectives, and results that reside in this field, and to explore what unites the research in such diverse contexts as, for example, the arts, conservation, or vocational craft education. The common thread between each of the chapters in the present book is the augmented attention given to methods—the craft research methods—and to the relationship between the field of inquiry and the field of practice. A common feature is that practice plays an instrumental role in the research found within the chapters, and that the researchers in this publication are also practitioners. The authors are researchers but they are also potters, waiters, carpenters, gardeners, textile artists, boat builders, smiths, building conservators, painting restorers, furniture designers, illustrators, and media designers. The researchers contribute from different research fields, like craft education, meal sciences, and conservation crafts, and from particular craft subjects, like boat-building and weaving. The main contribution of this book is that it collects together a number of related case studies and presents a reflection on concepts, perspectives, and methods in the general fields of craft research from the point of view of craft practitioners. It adds to the existing academic discussion of crafts through its wider acknowledgement of craftsmanship and extends its borders and its discourse outside the arts and crafts context. This book provides a platform from which to develop context-appropriate research strategies and to associate with the Craft Sciences beyond the borders of faculties and disciplines.